The Effect Of Taxpayer Awareness, Tax Sanctions, And Tax Knowledge On Taxpayer Compliance In Paying Land And Building Tax - Amiroh Nabila (Universitas Muhammadiyah Makassar, 2022)
The purpose of this study is to examine and determine the effect of taxpayer awareness, tax sanctions and tax knowledge simultaneously or partially on taxpayer compliance in paying Land and Building Tax. The population of this study is all Land and Building Taxpayers. The sample taken is 53 respondents. The type of data used is primary data. The data collection technique used is the questionnaire method, namely spreading (questionnaire). The data analysis technique used is the analysis method using multiple regression analysis, the coefficient of determination (adjusted R2). F test and t test. The results of this study are taxpayer awareness has a positive effect on taxpayer compliance in the Tangerang city area. Tax sanctions have a positive but not significant effect on taxpayer compliance in the Tangerang City area. Tax compliance has a positive effect on taxpayer compliance in the Tangerang City area. This study aims to reveal taxpayer awareness, tax sanctions, and tax knowledge on taxpayer compliance in paying land and building taxes. Taxpayer awareness has a positive and significant impact on taxpayer compliance in the area Tangerang City. Tax sanctions have a positive but not significant effect on taxpayer compliance in the Tangerang City area. Tax compliance has a positive and significant effect on taxpayer compliance